2015
DOI: 10.1038/srep14747
|View full text |Cite
|
Sign up to set email alerts
|

HDAC inhibitor misprocesses bantam oncomiRNA, but stimulates hid induced apoptotic pathway

Abstract: Apoptosis or programmed cell death is critical for embryogenesis and tissue homeostasis. Uncontrolled apoptosis leads to different human disorders including immunodeficiency, autoimmune disorder and cancer. Several small molecules that control apoptosis have been identified. Here, we have shown the functional role of triazole derivative (DCPTN-PT) that acts as a potent HDAC inhibitor and mis-express proto onco microRNA (miRNA) bantam. To further understanding the mechanism of action of the molecule in apoptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The average height of the nanopillar is about 1 µm (aspect ratio > 10) and the average interval is about 120 nm. This structural topology is consistent with those highly efficient bactericidal nanopatterned surfaces . Figure a–d shows the scanning electron microscope (SEM) images of ZnO nanopillars on glass, titanium and zinc foil (see supporting information for the images of ZnO nanopillar on other substrates, Figure S1 in the Supporting Information).…”
supporting
confidence: 84%
See 2 more Smart Citations
“…The average height of the nanopillar is about 1 µm (aspect ratio > 10) and the average interval is about 120 nm. This structural topology is consistent with those highly efficient bactericidal nanopatterned surfaces . Figure a–d shows the scanning electron microscope (SEM) images of ZnO nanopillars on glass, titanium and zinc foil (see supporting information for the images of ZnO nanopillar on other substrates, Figure S1 in the Supporting Information).…”
supporting
confidence: 84%
“…Recently, it was reported that cicada and dragonfly wing surfaces are covered with dense patterns of nanoscale pillar arrays that prevent bacterial growth by rupturing adhered microbial cells . It was also proved that a purely physical interaction between the cells and synthetic nanopatterns such as black silicon surfaces also results in cell deformation and massive lysis without the need for additional external chemicals or mechanical intervention . This new discovery opens up a great opportunity for the development of innovative microbicide surface technologies which are clean and safe, require no external chemicals and have no resistance issue.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Experimental evidence has shown that several cell cycle genes along with checkpoint kinase1-targeted cardiomyocyte proliferation can occur by regulation of miR-195 (107). Interestingly, miR-195 inhibition by LNA-modified anti-miRs in pigs and mice showed steady effects on heart regeneration, whereas treated animals were devoid of myocardial infarction (108 (86,87). Experimental data support that the mitochondrial regulatory pathway in human cancer cell lines can be affected by HDAC inhibitor, which suggests a conservative feature of apoptosis between Drosophila and humans.…”
Section: Microrna In Cardiac Diseases and Heart Regenerationmentioning
confidence: 99%
“…The class III HDACs (comprising SIRT 1-7) are related to the yeast protein Sir2 and their activities are depended on NAD + concentration [4,5]. The exact physiological role of these HDAC subtypes in cells is far from being completely elucidated, however, the division of labor among them has been studied using knockout and transgenic mice and RNAi techniques, in which, class I and class II are the most well studied [6,7]. The knockout of HDAC1 in mice caused cell proliferation defects and developmental retardation, and this unique function cannot be compensated by HDAC2 and HDAC3 [8,9].…”
Section: Introductionmentioning
confidence: 99%